2020
DOI: 10.1609/aaai.v34i05.6232
|View full text |Cite
|
Sign up to set email alerts
|

Story Realization: Expanding Plot Events into Sentences

Abstract: Neural network based approaches to automated story plot generation attempt to learn how to generate novel plots from a corpus of natural language plot summaries. Prior work has shown that a semantic abstraction of sentences called events improves neural plot generation and and allows one to decompose the problem into: (1) the generation of a sequence of events (event-to-event) and (2) the transformation of these events into natural language sentences (event-to-sentence). However, typical neural language genera… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 15 publications
0
54
0
Order By: Relevance
“…However, researchers realize that word-by-word generation models cannot efficiently model the long dependency across sentences (See et al, 2019). Models using intermediate representations as guidance to generate stories are then proposed (Yao et al, 2019;Martin et al, 2018;Ammanabrolu et al, 2020;Fan et al, 2019;. These works are developed toward short stories and thus are insufficient for modeling novels (See Section 1).…”
Section: Related Workmentioning
confidence: 99%
“…However, researchers realize that word-by-word generation models cannot efficiently model the long dependency across sentences (See et al, 2019). Models using intermediate representations as guidance to generate stories are then proposed (Yao et al, 2019;Martin et al, 2018;Ammanabrolu et al, 2020;Fan et al, 2019;. These works are developed toward short stories and thus are insufficient for modeling novels (See Section 1).…”
Section: Related Workmentioning
confidence: 99%
“…To make a long story more coherent, recent work proposes to generate a skeleton and then generate the full text guided by the skeleton. The skeleton could be a sequence of SRL frames (Fan et al, 2019), a sequence of event structure (subject, verb, object, preposition, modifier) (Ammanabrolu et al, 2020), a story premise (Fan et al, 2018), or a story summary (Chen et al, 2019). Users can revise the skeleton to control the generated text, but the approaches assume the existence of the skeleton extractor or labels in the training corpus.…”
Section: Related Workmentioning
confidence: 99%
“…If we add the phrase 'on the first day of the 18th century', the prediction becomes card, which matches the time setting. Ammanabrolu et al (2019) proposed an ensemble-based model to generate sentences given plot events. This involves two steps.…”
Section: Modelsmentioning
confidence: 99%
“…The next step is to expand these events to a story. We plan to experiment with the ensemble model by Ammanabrolu et al (2019) which is reported to combine the strength of the retrieve-and-edit method (Hashimoto et al, 2018), the template filling method, the sequence-to-sequence methods with finite state machine decoder, Monte Carlo beam decoding, and vanilla beam-decoding respectively. This method will conduct an event-to-event generation first to include more events before generating the output story.…”
Section: Modelsmentioning
confidence: 99%